Sentidos, comprometimento, consentimento e engajamento no trabalho: um estudo com jovens aprendizes brasileiros - Silas Dias Mendes Costa (2023)
This thesis aims to analyze how the meanings of work are related to commitment and consent bonds, as well as work engagement. It also explores how these bonds are connected to engagement, with a focus on young apprentices. Therefore, a quantitative study was carried out, of a descriptive and explanatory nature, whose data were collected through an electronic questionnaire. The choice of the public in question took into account suggestions from previous studies, which converge on the need to deepen studies with young workers, especially apprentices, whose nature of work and contract with organizations have specificities determined by a set of norms legal, updated by Decree No. 11.061/2022. In turn, the theoretical articulation between the meanings of work, commitment, consent and engagement, as proposed in the aforementioned thesis, seems to be unprecedented in relation to previous studies, which represents a gap to be filled, making it possible to test theoretical assumptions and analytical biases that can be incorporated into the theories used, either through their ratification or refutation. With a view to making the research viable, responses were collected from 2543 apprentices inserted in organizations from all regions of the country. As for the research instruments, it was decided to use validated questionnaires widely used in research on the themes, namely: the “Scale of Work with Meaning”, the “Measure of Organizational Commitment” – complete version; the “Organizational Consent Scale” and the “Utrecht Work Engagement Scale”. Social, demographic and professional data were also collected in order to present a profile of the research participants. From the point of view of the method, the instruments were submitted to confirmatory factor analysis, allowing the psychometric indicators to be analyzed from the researched public. In the next phase, after validating the items and factor(s) in each construct, descriptive statistics were used, interpreting the results according to the guidelines presented by the authors who validated the instruments. Finally, causal relationships were tested using the structural equation modeling technique with partial least squares. Of the 21 hypotheses tested, 18 were validated. The results provide theoretical and empirical support for the presented thesis argument, in which it is proposed that: “the meanings of work have a positive relationship with the bonds of commitment and consent and with engagement at work, and such bonds have a positive relationship with engagement at work” and indicating the following contributions: i) the proposition of an integrated theoretical model allowed testing some assumptions established from the literature, moving forward with discussions on the themes and the group of workers surveyed; ii) the validation and/or refutation of such assumptions – see hypothesis tests – made it possible to revisit the theories used, identifying particularities in the attribution of meanings to work and in the individual-organization bonds; iii) the analysis of the instruments used in the research revealed psychometric indices that attest to their applicability to the researched public; iv) the national scope of the research increases the possibility of generalizing the findings and, at the same time, opens space for new studies that focus on the plurality of this group, whether considering geographical issues, social or professional markers and; v) the research resulted in a return of the findings of this research through a report, in accessible language, sent to the institution that mediates the employment contract of these young people with the organizations, breaking the boundaries of academic discussions to a pragmatic-organizational perspective. The end of the research describes its limitations and a research agenda that can serve as a guide for conducting new studies, on the themes or public, in an individualized or articulated way.